Blocking NF-κB Activation in Ly6c(+) Monocytes Attenuates Necrotizing Enterocolitis - Managlia, Elizabeth (Am J Pathol, 2019)
Necrotizing enterocolitis (NEC) is a devastating disease affecting premature infants with intestinal inflammation and necrosis. The neonatal intestinal inflammatory response is rich in macrophages, and blood monocyte count is low in human NEC. We previously found that NF-κB mediates the intestinal injury in experimental NEC. However, the role of NF-κB in myeloid cells during NEC remains unclear. Herein, inhibitor of kappaB kinase β (IKKβ), a critical kinase mediating NF-κB activation, was deleted in lysozyme M (Lysm)–expressing cells, which were found to be Cd11b(+)Ly6c(+) monocytes but not Cd11b(+)Ly6c(−) macrophages in the dam-fed neonatal mouse intestine. NEC induced differentiation of monocytes into intestinal macrophages and up-regulation of monocyte recruitment genes (eg, L-selectin) in the macrophage compartment in wild-type mice, but not in pups with IKKβ deletion in Lysm(+) cells. Thus, NF-κB is required for NEC-induced monocyte activation, recruitment, and differentiation in neonatal intestines. Furthermore, pups with Lysm-IKKβ deletion had improved survival and decreased incidence of severe NEC compared with littermate controls. Decreased NEC severity was not associated with an improved intestinal barrier. In contrast, NEC was unabated in mice with IKKβ deletion in intestinal epithelial cells. Together, these data suggest that recruitment of Ly6c(+) monocytes into the intestine, NF-κB activation in these cells, and differentiation of Ly6c(+) monocytes into macrophages are critical cellular and molecular events in NEC development to promote disease.